2016
DOI: 10.1080/13218719.2016.1220037
|View full text |Cite
|
Sign up to set email alerts
|

The Law Is Not as Blind as It Seems: Relative Rates of Vicarious Trauma among Lawyers and Mental Health Professionals

Abstract: Professionals who are exposed to trauma through work may indirectly experience distress and traumatisation of their own, often referred to as vicarious traumatisation (VT). Little research has been directed toward the experience of VT among lawyers, especially in terms of how it compares with the VT experienced by mental health professionals (MHPs). This study compares the extent to which exposure to traumatic information affects professionals of different disciplinary backgrounds. Additionally, personality tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 31 publications
2
43
1
Order By: Relevance
“…Significantly higher levels of vicarious trauma have been identified in criminal lawyers compared to non-criminal lawyers, evidenced by PTSD-like symptoms (Vrklevski & Franklin, 2008). Similarly, compared to mental health practitioners, Australian lawyers exposed to traumatic material at comparable levels showed significantly higher STS scores (Maguire & Byrne, 2017). Their results suggest that organizational factors may have more influence than personality factors on how helpers respond to clients' traumatic material.…”
Section: Lawyers and Compassion Fatiguementioning
confidence: 93%
“…Significantly higher levels of vicarious trauma have been identified in criminal lawyers compared to non-criminal lawyers, evidenced by PTSD-like symptoms (Vrklevski & Franklin, 2008). Similarly, compared to mental health practitioners, Australian lawyers exposed to traumatic material at comparable levels showed significantly higher STS scores (Maguire & Byrne, 2017). Their results suggest that organizational factors may have more influence than personality factors on how helpers respond to clients' traumatic material.…”
Section: Lawyers and Compassion Fatiguementioning
confidence: 93%
“…Levin et al (2012) reported such association with age. Female gender was associated with more symptoms by Levin and Greisberg (2003) and Leclerc et al (2019), but Goldman (2006), Piwowarczyk et al (2009), Levin et al (2012), and Maguire and Byrne (2017) reported no such results. Levin and Greisberg (2003) found that prior treatment for mental health issues was associated with greater symptom severity.…”
Section: Risk Factors For Ptsd Symptomsmentioning
confidence: 93%
“…A higher caseload involving traumatic material or working with more trauma-related clients were related to higher symptom severity by Levin and Greisberg (2003), Goldman (2006), Levin et al (2011), and Leclerc et al (2019), but not by Sokol (2014). A history of prior trauma exposure in the personal life of the lawyers was also associated with the development of PTSD symptoms by Goldman (2006), Vrklevski and Franklin (2008), Maguire and Byrne (2017), and Leclerc et al (2019), but Piwowarczyk et al (2009) reported no association. Longer hours worked weekly was identified as influencing the increase of PTSD symptoms by Goldman (2006), Piwowarczyk et al (2009), Levin et al (2011), and Leclerc et al (2019).…”
Section: Risk Factors For Ptsd Symptomsmentioning
confidence: 97%
See 1 more Smart Citation
“…While differences may exist between VT and secondary trauma, for the purpose of this study we will use the terms interchangeably. First linked to psychotherapy work, it is now recognised that VT can occur in any area of health and social care (Devilly, Wright, & Varker, 2009) or in anyone working with trauma survivors or sufferers such as lawyers (Maguire & Byrne, 2017).…”
Section: Vicarious Traumamentioning
confidence: 99%